'Not all socialists dress the same': Menswear as cultural capital in China. Issue 1 (1st October 2021) - Bednall, Anthony Lawrence
Chinese sartorial style, like many cultures, has been defined, formalized and articulated to its population by hierarchical definition and visual association. Menswear styles have transitioned from strict Imperial codes, to westernized adoption, designed to shape a new modernism, as various leadership regimes imposed and defined dress codes to implement political and cultural structures. Sustainable practices were developed through the design and construction methods of Imperial garments and as a response to low resources, famine and inefficient management systems during the early years of the People's Republic of China. This period was characterized by rationing for fabrics, recycling and the re-invention of existing garments. Through a contemporary lens, this can be viewed as an integrated sustainable approach to the mass clothing of a significantly sized population. However, intervening regimes including the post-Imperial Nationalist leadership and the post-Mao Communist leadership cultivated a new visual identity for the Chinese population as westernization became the prefix for modernization. This article aims to map the historical development of menswear as cultural capital in China, to contextualize sustainable practices in the production of garments and define how these practices were systematically and repeatedly rejected in favour of new consumerism. It also aims to historically define the role of menswear in China as a representation of the nation's outward-facing international image and ambitions as a serious and contemporary player, within the global political and cultural community.